Heuristics and usability of a video assessment evaluation tool for teachers - Cruz, Sara (2020)
The article presents the design and development of an organized multimedia Web tool to help teachers evaluate videos produced by students according to the JuxtaLearn learning process. We use a development research methodology, fulfilling the following phases of the protocol: (1) preliminary investigation, (2) theoretical embedding, (3) empirical testing and (4) documentation, analysis and reflection on process and outcomes. We started with the exploratory analysis phase where it was intended to survey and identify the knowledge of a group of teachers about the scientificity and pedagogical potential of the video, to understand their difficulties and suggestions. Based on the data obtained in this phase, the tool was designed and further developed. Usability evaluation tests were carried out with experts and the target audience in order to adapt the product. Based on the results of usability testing, we can say that the prototype responded to the teachers' needs, arousing their interest in promoting video production with their students.